Nurse's Perception of Patient Safety Culture in an Effort to Improve Service Quality in the Operating Room of Riau Province Hospital - Yulisnawati; Zulfendri; Siti Saidah Nasution (Britain International for Academic Research (BIAR) Publisher, 2020)
The aim of the study is to find out Nurse's perception of patient safety culture in an effort to improve service quality. This study uses qualitative research methods with a phenomenological approach. The result of the study is obtained that the informants assume that the socialization carried out by the hospital in the context of increasing knowledge related to patient safety is not effective. Education and training for patient safety is carried out continuously to increase knowledge, improve and maintain staff competence. While the socialization carried out by the hospital did not have much influence to increase the informant's knowledge related to patient safety.